Nucleolar and spindle associated protein 1 promotes metastasis of cervical carcinoma cells by activating Wnt/β-catenin signaling - Han Li; Weijing Zhang; Ming Yan; Jiaqi Qiu; Jueming Chen; Xiaoying Sun; Xiangfu Chen; Libing Song; Yanna Zhang (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background The primary obstacle to treat cervical cancer is its high prevalence of metastasis, which severely affects patients’ quality of life and survival time. Nucleolar and spindle associated protein 1 (NUSAP1) has been implicated in the development, progression, and metastasis in several types of cancer. However, its oncogenic role in cervical cancer remains unclear. Methods Western blot assay and immunohistochemistry were used to determine the expression of NUSAP1 in 21 clinical fresh Cervical cancer tissues and 233 clinicopathologically characterized cervical cancer specimens. The biological roles of NUSAP1 in the metastasis of cervical cancer were investigated both in vitro by EMT, Side population analysis and Transwell assays and so on, and in vivo using a mouse 4w model of hematogenous metastasis and lymph node metastasis. Bioinformatics analysis, luciferase reporter analysis, immunoprecipitation and immunoblotting of nuclear and cytoplasmic cellular fractions were applied to discern and examine the relationshipbetween NUSAP1 and its potential targets. Results The results demonstrated that NUSAP1 was upregulated in cervical cancer cells and tissues, correlated positively with metastasis and poor clinical outcome of patients. High expression of NUSAP1 promoted metastasis by enhancing cancer stem cell (CSC) traits and epithelial-mesenchyme transition (EMT) progression, while silencing of NUSAP1 reduced CSC traits and EMT progression. Mechanistically, upregulation of NUSAP1 induced SUMOylation of TCF4 via interacting with SUMO E3 ligase Ran-binding protein 2 (RanBP2) and hyperactivated Wnt/β-catenin signaling in cervical cancer cells. Additionally, NUSAP1-induced cervical cancer cells metastasis and the cancer stem cell phenotype were abrogated with the Wnt/β-catenin signaling inhibitor XAV-939 treatment. Importantly, co-therapy of conventional treatment and XAV-939 will provide a novel and effective treatment for NUSAP1-ovexpressed cervical cancer patients. Conclusions Our results demonstrate thatNUSAP1 upregulation contributes to metastasis of cervical cancer by promoting CSC properties and EMT via Wnt/β-catenin signaling and XAV-939 might serve as a potential tailored therapeutic option for patients with NUSAP1-ovexpressed cervical cancer.